2000
DOI: 10.1002/1521-4141(200003)30:3<858::aid-immu858>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and protein analysis of divergent forms of the complement component C3 from a bony fish, the common carp (Cyprinus carpio): presence of variants lacking the catalytic histidine

Abstract: Unlike mammals, some bony fish species have been reported to possess multiple forms of the complement component C3. To explore the structural and functional diversity of bony fish C3, we have isolated eight distinct cDNA clones encoding C3 from a single carp (Cypri-nus carpio). The eight sequences were grouped into five C3 types, designated C3-H1, C3-H2, C3-S, C3-Q1 and C3-Q2, each sharing 80-86 % amino acid sequence identity with the others. A striking amino acid substitution was noted at the position corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 9 publications
4
30
2
Order By: Relevance
“…3A), purified carp C3 reacted with the anti-C3 antibody in several bands. The bands over 120 kDa in size are consistent with unreduced C3 protein, the two bands at approximately 115 kDa correspond to the a-chain and the band at approximately 60 kDa corresponds to the b-chain of the carp C3 protein [17]. C3 protein (only the b-chain) was already present in unfertilised eggs.…”
Section: The Appearance Of C3 Protein In Carp Ontogenymentioning
confidence: 55%
“…3A), purified carp C3 reacted with the anti-C3 antibody in several bands. The bands over 120 kDa in size are consistent with unreduced C3 protein, the two bands at approximately 115 kDa correspond to the a-chain and the band at approximately 60 kDa corresponds to the b-chain of the carp C3 protein [17]. C3 protein (only the b-chain) was already present in unfertilised eggs.…”
Section: The Appearance Of C3 Protein In Carp Ontogenymentioning
confidence: 55%
“…Interestingly, this important domain was not found in the second isoform of European seabass. Previous studies on carp, showed the existence of an isoform without anaphylotoxin domain and more similar to human C3 rather than to carp C3-Q2 isoform [28] indicating a possible different functional role of this isoform.…”
Section: Discussionmentioning
confidence: 88%
“…For example, the rainbow trout, a quasi-tetraploid species, contains at least 3 different isoforms of C3 [25]. Multiple C3 isoforms have also been characterized in the Gilthead seabream at protein level [26,27] while in the common carp up to eight C3 forms have been described [28]. Unlike mammals, it has been demonstrated that some species of teleost possess multiple forms of functionally active C3 that may be the products of several genes and may vary in their ability to bind to various surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, and as shown in mammals, it is likely that the architecture of the microbial surface would be an important factor in determining the binding of Hf or Bf/C2 to the C3b isoform newly bound into that surface [97]. In addition to being present in multiple isoforms, C3 has also been found to be polymorphic in carp [40]. Although it is tempting to speculate about possible functional differences among the polymorphic C3 forms, this intriguing idea remains to be further investigated in carp and other teleosts.…”
Section: C2/bf and Factor D Moleculesmentioning
confidence: 95%
“…It has been suggested that differences in these residues account, at least in part, for the variations in the binding efficiencies of the various trout C3 isoforms [96]. The situation in the carp C3 isoforms is similar although the residue differences appear to occur only at the position equivalent to human His 1126 [40]. It will be important in the future to determine whether the variations in binding are solely due to changes in the aforementioned residues, or whether other residues and domains in the C3 protein are also involved.…”
Section: C2/bf and Factor D Moleculesmentioning
confidence: 99%